Vitamin D 3 and calcium carbonate supplementation for adolescents with HIV to reduce musculoskeletal morbidity and immunopathology (VITALITY trial): study protocol for a randomised placebo-controlled trial - Dzavakwa, NV; Chisenga, M; McHugh, G; Filteau, S; Gregson, CL; Kasonka, L; Kranzer, K; Mabuda, HB; Mujuru, H; Redzo, N; Rowland-Jones, S; Schaible, UE; et al. (BioMed Central, 2022)
Background: Of the 2 million children living with HIV globally, 90% live in sub-Saharan Africa. Despite antiretroviral therapy, longstanding HIV infection is associated with several chronic complications in children including growth failure, particularly stunting and delayed puberty. Vitamin D deficiency, which is highly prevalent among children living with HIV in sub-Saharan Africa, has a further adverse impact on bone health. This trial aims to establish whether supplementation with vitamin D3 and calcium carbonate improves musculoskeletal health among peripubertal children living with HIV. Methods/design: We will conduct an individually randomised, double-blinded, placebo-controlled trial of weekly high-dose vitamin D3 (20,000 IU) plus daily calcium carbonate (500mg) supplementation for 48 weeks. Eight hundred and forty children living with HIV aged 11–19 years taking ART for ≥6 months will be enrolled and followed up for 96 weeks. The primary outcome is total body less-head bone mineral content for lean mass adjusted for height (TBLH-BMCLBM) Z-score at 48 weeks, measured by dual-energy X-ray absorptiometry (DEXA). Secondary outcomes are DEXA-measured lumbar spine bone mineral apparent density Z-score, number of respiratory infections, lean muscle mass and grip strength at 48 and 96 weeks and TBLH-BMCLBMZ-scores at 96 weeks. Sub-studies will investigate the effect of the intervention on vitamin D3 pathway metabolites and markers of bone turnover, intestinal microbiota, and innate and acquired immune function. Discussion: This is the largest trial to date of vitamin D supplementation in children living with HIV. Intervening to address deficits in bone accrual in childhood is critical for optimising adolescent and early adult bone health and prevention of later adult osteoporotic fractures. Trial results will draw attention to the need to screen for and treat long-term comorbidities in children living with HIV in resource-limited settings. Trial registration: Pan African Clinical Trials Registry PACTR20200989766029. Registered on 3 September 2020